Greek New Testament manuscripts from Albania - LaFleur, Didier (New testament tools, studies and documents, 2018)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎Abbreviations -- ‎List of Figures and Plates -- ‎Figures -- ‎Plates -- ‎Chapter 1. Introduction -- ‎1. History and Context -- ‎2. Aim and Methodology -- ‎Part 1. Greek Manuscripts from Albania: A Historical Background -- ‎Chapter 2. Greek Manuscripts from Albania: A Historical Background -- ‎1. Ἄνθιμος Ἀλεξούδης (1868) -- ‎2. Louis Duchesne and Pierre Batiffol (1885, 1887) -- ‎3. Ἄνθιμος Ἀλεξούδης (1892, 1898, 1900-1901) and the Σκουριπέκης' Chronicle -- ‎4. Hermann von Soden and Caspar René Gregory (1902, 1908) -- ‎5. Νίκος Α. Βέης (1952) -- ‎6. Johannes Koder and Erich Trapp (1968) -- ‎7. Theofan Popa (2003) -- ‎8. History of the Fonds 488: Elements and Hypotheses -- ‎9. The Rediscovery of Beratinus 1 and Beratinus 2 and Their Chinese Restorers (1968-1972) -- ‎Part 2. The Manuscripts -- ‎Chapter 3. Albanian National Archives 1 (pl. 1) -- ‎1. Physical Description (Original) -- ‎2. Physical Description (Facsimiles) -- ‎3. Contents -- ‎4. Textual Features -- ‎5. Variant Readings -- ‎6. Bibliography -- ‎Appendix 1: Table Concordance according to Boxes 1 to 9 -- ‎Appendix 2: Supposed Former Flyleaves from Beratinus 1 (re uera Flyleaves from ANA 12) -- ‎Appendix 3: Historical Account of the Rediscovery and Restoration of Beratinus 1 and Beratinus 2 in the People's Republic of China -- ‎Chapter 4. Albanian National Archives 2 (pl. 2-3) -- ‎1. Physical Description (Original) -- ‎2. Physical Description (Facsimiles) -- ‎3. Contents -- ‎4. Textual Features -- ‎5. Variant Readings -- ‎6. Bibliography -- ‎Appendix: Table Concordance according to Boxes 1 to 21 -- ‎Chapter 5. Albanian National Archives 4 (pl. 5-6) -- ‎1. Physical Description -- ‎2. Contents -- ‎3. Textual Features -- ‎4. Variant Readings -- ‎5. Bibliography -- ‎Chapter 6. Albanian National Archives 5 (pl. 7) -- ‎1. Physical Description.